Spatial variation of locational patterns of shadow economies in the city of Baqubah - Kadhim, Ayat; Abdullah, Senaa (Al-Adab Journal, 2024)
Baquba city is one of the Diyala governorate cities which is characterized by concentration of urban activities that distribute into a various Shapes and patterns of distribution consequently, this development of urban activities and its concentration inside the city has accompanied with emersion of the phenomenon of Shadow economics Boths and selling display tables which has greatly become precent and widespread to a large extent in the most areas of the city , thus it involved varied types and it multiplied and increased in size, occupied unallocated places and dominated the streets pavements part of the street and empty places , these booths has expanded over the main and subsidiary streets of the city and the streets of the residential areas, public markets, city center and even inside residential district until the size activity has reached (1172) an urban economic activity shaped as Boths and selling display tables what made them take seven patterns locating patterns in their spread where the subsidiary streets occupied the first rank in the size of these overstepping activities followed by in the second rank the central commercial district and the main commercial streets after which these Boths coms within the public markets in the rate and size of its spread and the gathered shadow economics in the last rank coms the widespread and scattered shadow economics inside the local district .